A utilização de aplicativos para smartphones como recurso didático no ensino de ligações químicas para a 1ª série do ensino médio - Rodrigues, Ana Maria de Oliveira (2022)
The teaching of chemistry in Brazil, especially at the secondary level, has distinguished itself in educational research by seeking a better understanding of the teaching and study of chemistry, developing methodological proposals and teaching tools that can help to make lessons more enjoyable and increase the learning level of students. Chemistry as a subject is perceived by many students as decontextualized and decorative, so chemistry teaching in many schools urgently needs to undergo changes in the teaching and learning process. One of them is the use of didactic resources to enhance student learning and give them a better impression. Among these resources are the technological means that are present in society and in the daily lives of students. Smartphones stand out in this scenario due to their popularity in recent years, since there are applications on these mobile devices that make them very popular and widely used. Thus, this study presents the possibility of using these applications for mobile devices, especially smartphones, as didactic aids in chemistry lessons. The study in question was conducted with students at an all-day school in the city of Fortaleza/ CE in 2020. To this end, questionnaires were used throughout the study to collect data in order to verify how the applications can contribute to the teaching of chemistry. As far as the quantitative aspects are concerned, the results obtained were ambiguous in terms of their application to improve learning. This is probably due to the fact that these analyses had different perspectives in data collection, as the number of participants varied in the different phases of the research. It was observed that in the situations where the applications were used, there was an improvement in learning of some content. We concluded that the use of applications showed great potential as a didactic resource, presenting a high level of acceptance by the students and enabling future researches, and that this study also be used as a proposal to support teachers of basic education when adopting the use of technologies in a significant and creative way in the teaching of chemistry.